Preparation method and application of plasma modified zinc-doped nickel sulfide
The zinc-doped Ni3S2 nanosheet array electrocatalyst synthesized and plasma-modified by two-step hydrothermal method solves the problem of low OER activity in electrochemical water decomposition, and achieves efficient redox reactions and dye degradation in alkaline electrolytes, meeting the dual needs of energy and environment.
Patent Information
- Application Number
- CN202211209714.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-30
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-09-30
AI Technical Summary
The prior art has low activity in electrochemical water decomposition and scarce catalysts, making it difficult to effectively treat dye degradation in printing and dyeing wastewater.
The zinc-doped Ni3S2 nanosheet array was synthesized by a two-step hydrothermal method and plasma modification was performed to prepare a PA@Zn-Ni3S2/NF electrocatalyst for improving redox reaction activity in alkaline electrolytes and degrading dyes.
The redox reaction was carried out in the alkaline electrolyte at a low overpotential (192mV), which significantly improved the activity of the catalyst, and degraded the dye wastewater by 94.91% under the combined system, meeting the dual needs of energy and environment.
Smart Images

Figure CN115957781B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a plasma modification method, and in particular to a preparation method and application of plasma modified zinc-doped nickel sulfide. Background Art
[0002] Due to the increase in energy consumption and environmental pollution, clean renewable energy must be sought to replace fossil fuels. Electrochemical water splitting is a promising way to produce hydrogen. However, the anodic oxygen evolution reaction (OER) is affected by sluggish kinetics and remains a key bottleneck for improving water splitting technology due to the involvement of a four-electron transfer process for O-O bond formation. Although IrO2 and RuO2 are the most active OER catalysts, their scarcity and high cost seriously hinder their widespread use. Nickel has become an interesting transition metal element due to its catalytic ability for water oxidation, and a lot of effort has been invested in the fabrication of nickel-based OER catalysts operating in alkaline media. It has been reported that element doping can regulate the valence state and chemical environment of the electrolyte.
[128] , and recent studies have suggested that the electrochemically active element Zn is an effective dopant to enhance the OER activity of nickel sulfide. Wastewater pollution in industrial production processes is also a major problem that needs to be solved urgently, especially the high chromaticity and difficult degradation of printing and dyeing wastewater. Therefore, it is also urgent to find a catalyst that meets both energy and environmental protection requirements. However, the use of non-toxic and non-electroactive Zn species as promoters to regulate the OER activity of nickel sulfide and simultaneously degrade dyes has not been reported before. In this chapter, Zn-doped Ni3S2 nanosheet arrays supported on NF (Zn-Ni3S2 / NF) were prepared and after plasma modification, they showed better activity in alkaline electrolytes and better degradation of dyes in the combined system. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a preparation method of plasma-modified molybdenum-doped nickel sulfide, which can prepare an efficient and stable Mo-doped Ni3S2 electrocatalyst on nickel foam. In the Mo-doped Ni3S2 structure, Mo ions embedded in Ni3S2 nanoparticles form a large number of Mo-S interface sites, and water decomposition is prepared and carried out at different temperatures, and the water with the best hydrogen decomposition effect is used for the treatment of dye wastewater.
[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0005] A method for preparing plasma-modified zinc-doped nickel sulfide comprises the following steps:
[0006] A method for preparing plasma-modified zinc-doped nickel sulfide comprises the following steps:
[0007] Step 1 Synthesis of nickel foam precursor: Dissolve Ni(CH3COO)2·4H2O, Zn(CH3COO)2·2H2O and urea in ultrapure water and stir to form a clear solution;
[0008] Step 2: Transfer the above solution and the cleaned nickel foam into a stainless steel autoclave, and heat them at 110-130° C. for 6-8 hours, and cool them naturally after the reaction is completed;
[0009] Step 3: Take out the obtained NF, wash it with ultrapure water and ethanol three times, and dry it in a vacuum oven;
[0010] Step 4: Immerse the nickel foam loaded with the precursor in a Na2S solution, then place the reacted solution in a stainless steel autoclave lined with polytetrafluoroethylene, react at 110-130° C. for 3-5 hours, take out the nickel foam, wash and dry;
[0011] Step 5: As a control, in step 1, Zn(CH3COO)2·2H2O was not added, and steps 1 to 4 were repeated to synthesize pure Ni3S2 / NF;
[0012] Step 6: Cut off part of the synthesized zinc-doped nickel sulfide and transfer it to the center of the dielectric barrier discharge reactor, and treat it under AC voltage for 50-70s to obtain PA@Zn-Ni3S2 / NF.
[0013] Preferably, in step 1, Ni(CH3COO)2·4H2O is 1 mmol and has a mass of 0.249 g, Zn(CH3COO)2·2H2O is 0.1 mmol and has a mass of 0.0220 g, urea is 10 mmol and has a mass of 0.6 g, and ultrapure water is 40 mL.
[0014] Preferably, in the step 2, the upper and lower bottom surfaces of the nickel foam are 3 cm×3 cm in size and 2 mm in thickness.
[0015] Preferably, the stainless steel high-pressure reactor in step 2 is 50 mL.
[0016] Preferably, the ethanol concentration in step three is 95%; the drying temperature in the vacuum oven is 60° C. and the drying time is 2 h.
[0017] Preferably, in step 4, the concentration of the Na2S solution is 0.2 mol / L and the volume is 40 mL.
[0018] Preferably, the stainless steel autoclave in step 4 is lined with polytetrafluoroethylene and has a volume of 50 mL.
[0019] Preferably, in step six, the AC voltage is 70V.
[0020] Preferably, the upper and lower bottom surfaces of the iron-doped nickel sulfide cut in step six are 1 cm×1 cm in size.
[0021] Preferably, a plasma-modified zinc-doped nickel sulfide is used to degrade acidic lake blue A wastewater.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present invention synthesized Zn-doped Ni3S2 by a two-step hydrothermal method, and then modified it by plasma to synthesize PA@Zn-Ni3S2 / NF, which can be used in both energy and environmental aspects. Zinc is an effective promoter for regulating the OER performance of Ni3S2, and the Zn-doped Ni3S2 nanoarray only requires an overpotential of 192 mV for the oxygen evolution reaction after plasma modification, which is 35 mV lower than that of Ni3S2 / NF nanoarray.
[0024] (2) The present invention uses response surface methodology to degrade dyes by combining plasma with the prepared catalyst. When the initial concentration is 100 mg / L, the pH is 7, the voltage is 90 V, and the conductivity is 1 mS / cm, the effect can reach 94.91%. It is a low-cost catalytic degradation combined system and provides a new method for improving the activity of sulfide under the electrocatalytic action of zinc on water oxidation. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 .XRD patterns of pure nickel sulfide, zinc-doped nickel sulfide and plasma-modified zinc-doped nickel sulfide;
[0026] Figure 2 XPS spectra of plasma-modified zinc-doped nickel sulfide (a) Full spectrum of PA@Zn-Ni3S2 / NF; (b) Zn2p; (c) Ni 2p; (d) S 2p;
[0027] Figure 3 .(ac) Ni3S2 / NF; (df) Zn-Ni3S2 / NF; (gi) SEM images of PA@Zn-Ni3S2 / NF; Figure (j) is the EDS spectrum of PA@Zn-Ni3S2 / NF;
[0028] Figure 4 .(a) TEM image of plasma-modified zinc-doped nickel sulfide; (b) HRTEM image of plasma-modified zinc-doped nickel sulfide; (c) Selected area electron diffraction pattern of plasma-modified zinc-doped nickel sulfide; (dh) Elemental mapping of plasma-modified zinc-doped nickel sulfide;
[0029] Figure 5 Electrochemical OER properties of the electrocatalyst in 1.0 M KOH solution (a) Scan rate 5 mV s-1 Polarization curves at 10 mA cm (iR correction), initial and after 1000 CV cycles (inset); (b) 10 mA cm -2 Overpotential corresponding to current density; (c) Tafel spectrum corresponding to each catalyst; (d) Electrochemical impedance spectroscopy (EIS) of various catalysts;
[0030] Figure 6 .Comparison chart of predicted value and actual value of dye degradation by plasma catalyst;
[0031] Figure 7 .Effect of the interaction between initial concentration and voltage on the degradation rate of Reactive Red X-3B in the combined system: contour plot; response surface;
[0032] Figure 8 .Effect of the interaction between initial concentration and pH on the degradation rate of Reactive Red X-3B in the combined system: contour plot; response surface;
[0033] Fig. 9 .Effect of the interaction between initial concentration and conductivity on the degradation rate of Reactive Red X-3B in the combined system: contour plot; response surface;
[0034] Fig.10 .Effect of the interaction between voltage and pH on the degradation rate of Reactive Red X-3B in the combined system: contour plot; response surface;
[0035] Fig.11 .Effect of the interaction between voltage and conductivity on the degradation rate of Reactive Red X-3B in the combined system: contour plot; response surface;
[0036] Fig.12 .The effect of the interaction of pH and conductivity on the degradation rate of Reactive Red X-3B in a combined system: contour plot; response surface. DETAILED DESCRIPTION
[0037] 1. Experimental part
[0038] 1. Experimental reagents and instruments
[0039] Table 1 Experimental reagents
[0040]
[0041] Table 2 Experimental instruments
[0042]
[0043]
[0044] 2. Sample characterization test
[0045] XRD patterns were obtained on a Bruker D8 Advance X-ray diffractometer with Cu Kα radiation. SEM images and EDS spectra were recorded with a Zeiss Gemini 300 microscope. High-resolution TEM and mapping analyses were performed using a JEOL JEM 2100F microscope. XPS spectra were obtained on a Thermo Kalpha photoelectron spectrometer.
[0046] 3. Material preparation method
[0047] A method for preparing plasma-modified zinc-doped nickel sulfide comprises the following steps:
[0048] Step 1 Synthesis of nickel foam precursor: 1 mmol, 0.249 g of Ni(CH3COO)2·4H2O, 0.1 mmol, 0.0220 g of Zn(CH3COO)2·2H2O and 10 mmol, 0.6 g of urea were dissolved in 40 mL of ultrapure water and stirred to form a clear solution;
[0049] Step 2: Transfer the above solution and the cleaned nickel foam with a size of 3 cm × 3 cm on the upper and lower bottom surfaces and a thickness of 2 mm into a 50 mL stainless steel autoclave, and heat continuously at 120° C. for 7 hours, and cool naturally after the reaction is completed;
[0050] Step 3: Take out the obtained NF, wash it with ultrapure water and 95% ethanol three times, and dry it in a vacuum oven at 60°C for 2h;
[0051] Step 4: Immerse the nickel foam loaded with the precursor in 40 mL of a 0.2 mol / L Na2S solution, then place the reacted solution in a 50 mL polytetrafluoroethylene-lined stainless steel autoclave, react at 120° C. for 3 h, take out the nickel foam, wash it, and dry it;
[0052] Step 5: As a control, in step 1, Zn(CH3COO)2·2H2O was not added, and steps 1 to 4 were repeated to synthesize pure Ni3S2 / NF;
[0053] Step 6: Cut 1 cm × 1 cm of the synthesized zinc-doped nickel sulfide and transfer it to the center of the dielectric barrier discharge reactor, and treat it at an AC voltage of 70 V for 60 s to obtain PA@Zn-Ni3S2 / NF.
[0054] The plasma-modified zinc-doped nickel sulfide of the present invention is suitable for degrading acidic lake blue A wastewater.
[0055] 4. Electrochemical test
[0056] The tests were performed using a three-electrode system in 1 M KOH, with the catalyst-loaded NF acting as the working electrode, the counter electrode and the reference electrode being a graphite rod and an Ag / AgCl electrode, respectively. All initial data were calibrated using 85% iR compensation, and the potential of the reversible hydrogen electrode (RHE) was calculated using the following formula: E(vs.RHE) = E(vs.Ag / AgCl) + 0.197 + 0.059 × pH. Linear sweep voltammetry (LSV) and cyclic voltammetry (CV) were used to determine the activity of the catalyst for OER, respectively. Before recording, the catalyst was charged at 100 mV s -1 Scan until a stable cyclic voltammogram is obtained. -1 The linear sweep voltammetry curves were recorded at a scan rate of 1000 Å and the Tafel slope was obtained by plotting the overpotential versus log(J) from the LSV curves. Electrochemical impedance spectroscopy (EIS) was performed in the frequency range of 0.01 to 10 5 Recorded in Hz.
[0057] 5. Response surface catalytic degradation of dyes
[0058] The Box-Behnken design (BBD) was used to analyze the degradation process of active red X-3B by DBD combined catalyst PA@Zn-Ni3S2 / NF, with the decolorization rate of active red X-3B as the response value, denoted as Y, and the concentration, voltage, pH and conductivity as the action factors, denoted as A, B, C, and D respectively (Table 3). 29 groups of interactive experiments were designed to investigate the effects of the four factors on the degradation of active red X-3B and determine the optimal process conditions.
[0059] Table 3 Values and level ranges of each factor
[0060]
[0061] 2. Characterization and performance analysis of catalysts
[0062] 1. XRD analysis
[0063] PA@Zn-Ni3S2 / NF is prepared by a two-step hydrothermal method followed by plasma modification. Nickel foam is used as a substrate, which can serve as both a nickel source and a substrate. First, the precursor is synthesized by placing ultrapure water, nickel acetate, zinc acetate, urea and clean nickel foam into a stainless steel autoclave lined with polytetrafluoroethylene. After the precursor is synthesized, it is transferred to a reactor with a sodium sulfide solution to synthesize the final product. Finally, plasma treatment is performed. Figure 1X-ray diffraction (XRD) patterns of PA@Zn-Ni3S2 / NF, Zn-Ni3S2 / NF, and Ni3S2 / NF are shown. The peaks at 21.4° corresponding to (101), 30.8° corresponding to (110), 37.4° corresponding to (003), 49.4° corresponding to (113), and 54.9° corresponding to (122) of Ni3S2 / NF correspond to Ni3S2 (JCPDS No.44-1418), and the other peaks are from the nickel substrate. The incorporation of Zn does not change the crystal structure of Ni3S2 because their atomic sizes are similar, and the plasma modification does not affect its lattice planes. These observations indicate that plasma-modified Zn-doped Ni3S2 was successfully formed.
[0064] 2. XPS analysis
[0065] Figure 2 shows the X-ray photoelectron spectroscopy (XPS) survey spectrum of plasma-modified Zn-doped Ni3S2, Figure 2 a also further confirmed the presence of Zn, Ni and S elements. Figure 2 b shows the Zn 2p XPS spectrum. The two peaks at 1044.2 and 1021.2 eV can be attributed to Zn 2p 3 / 2 and Zn 2p 1 / 2 .like Figure 2 c, Ni 2p 3 / 2 and Ni 2p 1 / 2 The binding energy of Ni is at 855.3 and 872.9 eV. The satellite peaks at 860.8 and 879.0 eV are the vibrational peaks of Ni, such as Figure 2 As shown in Figure d, the peak at 168.0 eV can be attributed to the typical characteristics of Ni–O–S species with high oxidation state S, which is due to surface oxidation in air. 1 / 2 and S 2p 3 / 2 Two other peaks were also observed at 162.7 and 161.3 eV, respectively. In conclusion, XPS verified the formation of nickel sulfide and the doping of zinc.
[0066] 3. SEM analysis
[0067] The surface morphologies of samples prepared under different reaction conditions are shown in Figure 2. Figure 3 When pure Ni3S2 / NF is synthesized without adding zinc source in the reaction, the obtained Ni3S2 / NF has a relatively regular and compact sheet array structure, and the surface of the nanosheet is smooth ( Figure 3 ac). When the zinc source is added during the reaction, the resulting Zn-Ni3S2 still has a certain flake structure, but the originally smooth surface of the nanosheet has become very rough ( Figure 3df). It can be seen that after adding the zinc source, the obtained sample still presents a flaky structure but it is irregular and disordered. After the plasma shock, the flaky layer structure on the surface of the PA@Zn-Ni3S2 / NF sample becomes very fuzzy. This is because after the plasma treatment, the loose material attached to the surface of the flaky array becomes fluffy and covers the surface of the flaky array ( Figure 3 gi). At the same time, the sheets are firmly fixed on the nickel foam to form a very strong three-dimensional structure, making PA@Zn-Ni3S2 / NF a very strong and stable catalyst. EDS confirmed the presence of Zn, Ni and S elements in the sulfidation product ( Figure 3 j).
[0068] 4. TEM analysis
[0069] Figure 4 a shows a transmission electron microscopy (TEM) image of the nanosheet, showing its rough surface. Figure 4 b) The high-resolution TEM (HRTEM) image taken shows clear lattice fringes. The lattice fringes in the image are very clear and easy to identify. The interplanar spacing is 0.29nm, pointing to the (110) plane of the Ni3S2 phase; the interplanar spacing is 0.24nm, pointing to the (003) plane of the Ni3S2 phase; and the interplanar spacing is 0.18nm, pointing to the (113) plane of the Ni3S2 phase. Note that the HRTEM only shows the lattice fringes of the Ni3S2 phase, indicating that it is indeed a plasma-modified Zn-doped Ni3S2 compound, rather than a mixture of ZnS and Ni3S2. Figure 4 The bright rings composed of discrete points in the selected area electron diffraction (SAED) image of PA@Zn-Ni3S2 / NF in c can be well corresponded to the (1 1 3), (0 0 3), and (1 1 0) crystal planes. These characterizations fully demonstrate the successful formation of PA@Zn-Ni3S2 / NF, which is consistent with the XRD characterization. Figure 4 dh presents the elemental mapping of PA@Zn-Ni3S2 / NF, indicating the presence of Zn, Ni, and S. All these results support the successful synthesis of plasma-modified Zn-doped Ni3S2 nanosheet arrays.
[0070] 5. Catalytic performance of OER
[0071] The electrocatalytic OER performance of the catalyst PA@Zn-Ni3S2 / NF was tested in 1.0 M KOH using a typical three-electrode cell. For comparison, Zn-Ni3S2 / NF and Ni3S2 / NF were also measured under the same conditions. Unless otherwise specified, the ohmic potential drop (iR) loss due to solution resistance is applied to all initial data, and all potentials are reported on the reversible hydrogen electrode (RHE) scale. Figure 5 a shows the linear sweep voltammetry (LSV) curves of PA@Zn-Ni3S2 / NF, Zn-Ni3S2 / NF, and Ni3S2 / NF in 1.0 M KOH. PA@Zn-Ni3S2 / NF has good OER activity, requiring only an overpotential of 192 mV ( Figure 5 b) can reach 10mA cm -2 The overpotential is 19 and 35 mV lower than that of Zn-Ni3S2 / NF and Ni3S2 / NF, and the original catalytic performance can still be maintained after 1000 cycles. Figure 5 c shows the corresponding Tafel plots. The Tafel slopes of PA@Zn-Ni3S2 / NF, Zn-Ni3S2 / NF, and Ni3S2 / NF are 201, 227, and 266 mV dec, respectively. -1 The Tafel slope of PA@Zn-Ni3S2 / NF is lower than that of Zn-Ni3S2 / NF and Ni3S2 / NF, indicating that Zn doping after plasma modification can provide faster OER kinetics and higher performance, indicating that the OER activity can be rationally regulated by plasma. It can be concluded that PA@Zn-Ni3S2 / NF is an effective electrocatalyst for OER. To further understand the excellent OER activity of PA@Zn-Ni3S2 / NF, Figure 5 d The electrochemical impedance spectra (EIS) of PA@Zn-Ni3S2 / NF, Zn-Ni3S2 / NF and Ni3S2 / NF were measured. The EIS of PA@Zn-Ni3S2 / NF was 1.757Ω, which was smaller than the 2.974Ω and 4.122Ω of Zn-Ni3S2 / NF and Ni3S2 / NF, respectively. This result indicates that PA@Zn-Ni3S2 / NF has a smaller impedance, indicating that its electron transfer rate is higher, the reaction kinetics is higher, and it has more exposed catalytic active sites for OER catalysis.
[0072] 6. Degradation of Reactive Red X-3B by Response Surface Methodology Combined System
[0073] (1) Model establishment
[0074] Table 4 Experimental design
[0075]
[0076]
[0077] Using Design-Expert software, response surface plasma combined with PA@Zn-Ni3S2 / NF catalyst to degrade active red X-3B, 29 experimental schemes were designed using BBD, and experiments were carried out according to each set of process conditions and the decolorization rate of each degradation experiment was calculated. The results are shown in Table 4. The reaction time of the active red X-3B degradation process in the experiment was set to 180s.
[0078] According to the results in Table 4, the empirical relationship between the response amount (Y-degradation rate) and the independent variables (A-concentration, B-voltage, C-pH, D-conductivity) can be obtained as the following second-order polynomial equation:
[0079] Y=89.26-5.18A+9.57B-0.94C+2.39D
[0080] -3.15AB+2.82AC-0.88AD-2.80BC-4.75BD-2.20CD
[0081] -6.46A 2 -5.19B 2 -5.38C 2 -2.78D 2
[0082] (2) Analysis of variance
[0083] Table 5 Variance analysis table
[0084]
[0085]
[0086] From the equation and the variance analysis table, we can see that in the first-order terms, the initial concentration (A), voltage (B), and conductivity (D) are less than 0.0001, which indicates that these three parameters have a great influence on the effect of plasma combined with PA@Zn-Ni3S2 / NF catalyst on the degradation of active red X-3B dye. Among the two parameters that work together, the P value of BD is only 0.0002, which indicates that the combined effect of voltage and conductivity also has a great influence on the decolorization of active red X-3B dye. In the second-order terms, A 2 , B 2 , C 2The P value is less than 0.0001. In addition to the same findings as above, that is, these three items have a greater impact on the decolorization rate, according to the relationship that the influence of each parameter on the decolorization rate in the equation is proportional to the F value, it can be seen that the influence of a single factor on the decolorization rate of the solution is arranged as follows: B>A>D>C, that is, voltage>initial concentration>conductivity>pH. The P value of the model's lack of fit term is 0.1331, which is not significant. This phenomenon shows that there is no lack of fit factor in the experiment, the fitting effect is good, the experimental error is small, and the conclusion is highly credible. Figure 6 The actual degradation rate of the plasma-PA@Zn-Ni3S2 / NF catalyst for degradation of active red X-3B dye is close to the predicted value of the model, indicating that the quadratic response surface model analysis is very similar to the analysis of the real system experiment. The correct selection of the four factors (initial concentration, voltage, pH, and conductivity) in the experiment can effectively find the optimal degradation conditions.
[0087] (3) Analysis of the interaction between plasma DBD and PA@Zn-Ni3S2 / NF in the degradation of reactive red X-3B
[0088] 1) The interaction between solution concentration and voltage
[0089] Depend on Figure 7 It can be seen that when pH and conductivity are at intermediate values (pH = 7, conductivity = 3mS / cm), when the concentration of the reactive red X-3B dye solution is constant, the solution decolorization rate is proportional to the voltage, that is, when the concentration remains unchanged, the higher the voltage, the higher the solution decolorization rate. When the solution concentration is 50mg / L and the voltage is 90V, the decolorization rate is nearly 95%, which shows that the initial concentration has a greater impact on the decolorization rate than the voltage, and more active substances are produced under high voltage for catalyst utilization; when the original concentration is 100mg / L and the voltage is 70V, the decolorization rate can also exceed 90%; but as the initial concentration of the solution increases further, the effect of voltage on the decolorization rate becomes less and less obvious. When the dye solution concentration is 150mg / L, even if the voltage is increased to 90V, the decolorization rate does not exceed 80%. The P value of the interaction between initial concentration and voltage is 0.0058, which is consistent with the significance of the above analysis.
[0090] 2) The interaction between solution concentration and pH
[0091] Depend on Figure 8It can be seen that when the voltage and conductivity are in the middle value (U=70V, conductivity=3mS / cm), when the original concentration of reactive red X-3B dye is 100mg / L, pH=7, the solution decolorization rate exceeds 85%, close to 90%. This is the best effect of decolorization rate under the conditions of concentration and pH interaction. In the spatial coordinate system of initial concentration-pH-decolorization rate, the curve of degradation rate is a parabola, and the point where the highest point of the parabola is projected on the vertical axis is the highest decolorization rate, and the point projected on the two horizontal axes is the middle value of pH and concentration, which shows that these two interacting factors need moderate conditions to achieve the highest decolorization rate. When the initial concentration is 50mg / L or 150mg / L, the influence on the decolorization rate under acidic and alkaline conditions is not obvious, which shows that the influence of initial concentration on degradation rate is more significant than pH, which is consistent with the above analysis results.
[0092] 3) The interaction between solution concentration and conductivity
[0093] Depend on Fig. 9 It can be seen that the interaction between initial concentration and conductivity does not significantly affect the decolorization rate of the solution. When pH and voltage are at intermediate values (pH = 7, U = 70V), if the initial concentration of the solution is 100 mg / L, conductivity = 3 mS / cm, the decolorization rate of the solution is close to 90%, but whether the conductivity is low (1 mS / cm) or high (5 mS / cm), the decolorization rate of high concentration (150 mg / L) and low concentration (50 mg / L) solutions remains at a relatively high level (the lowest is maintained at more than 70%), and there is little difference. However, the decolorization effect of the high concentration solution is generally lower than that of the low concentration solution with the same other parameters. This is because in the high concentration solution, the number of dye molecules is large and cannot be completely degraded. The P value of these two interaction factors is high, which is consistent with the result that the two factors analyzed have little effect on the degradation rate.
[0094] 4) Interaction between voltage and pH
[0095] Depend on Fig.10 It can be seen that when the initial concentration of the reactive red X-3B dye solution is constant, the acidity and alkalinity are moderate (pH neutral), the higher the voltage (up to 90V), the higher the decolorization efficiency of the stock solution, close to 95%, which means that the decolorization efficiency of the dye is positively correlated with the voltage parameter. At the same time, the interaction factors of voltage and pH have a significant effect on the degradation efficiency, and the data analysis results above are consistent with this conclusion. The P value of this interaction is low, which is consistent with the theory. At the same time, we can also see from the 3D space diagram of this set of interactive factors that when the pH value changes, the degree of curvature of the surface changes less, and when the voltage changes from low to high, it can be seen that the change amplitude of the surface is very large, which shows that the effect of voltage on the decolorization rate is greater than pH.
[0096] 5) The interaction between voltage and conductivity
[0097] Depend on Fig.11 It can be seen that the combined effect of these two interactive factors has a significant effect on the decolorization rate of the reactive red X-3B dye solution, which is consistent with the conclusion drawn from the response surface experiment above (P=0.0002). The initial concentration and pH of the solution were selected to be in the middle value (initial concentration = 100 mg / L, pH = 7) for analysis: when the voltage was 70 V and the conductivity was 3 mS / cm, the decolorization rate of the original solution was close to 90%. When the conductivity is reduced to 1mS / cm, the decolorization rate of the original solution of Reactive Red X-3B increases significantly with the increase of voltage; when the conductivity is increased to 5mS / cm, although it is at a higher level at the beginning, the improvement of the decolorization rate is not particularly obvious with the increase of voltage, and it even decreases slightly at the end, indicating that high voltage and high conductivity will damage the catalyst under the discharge of plasma, thereby affecting the degradation effect. When the voltage is 70V and the conductivity is 3mS / cm, when the voltage is further increased to 90V, the decolorization rate is about 95%. That is to say, when the conductivity is constant, the voltage is proportional to the decolorization rate. When the voltage is constant, the conductivity is at a lower level, it is proportional to the decolorization rate. When the conductivity is at a higher level, it is inversely proportional to the decolorization rate. These phenomena verify two conclusions: first, voltage is the single factor that has the greatest impact on the decolorization rate of the solution, and its influence is far greater than that of conductivity; second, the interaction factors of voltage and conductivity have a very significant impact on the decolorization rate of the original dye solution, which is consistent with the data analysis above.
[0098] 6) Interaction between solution pH and conductivity
[0099] Depend on Fig.12 It can be seen that the initial concentration and voltage of the reactive red X-3B dye solution are both at the intermediate value (initial concentration = 100 mg / L, voltage = 70V) condition analysis: when the pH is the intermediate value 7 and the conductivity is the intermediate value 3mS / cm, the highest decolorization rate under the action of these two interactive factors exceeds 90%. Under the same pH, the greater the value of conductivity, the higher the decolorization rate of the original solution, but when the pH is greater than 7, as the pH further increases, regardless of whether the conductivity is high or low, the decolorization rate is slightly different, but the change tends to be gentle, and even slightly decreases. Under low pH conditions, the effect of conductivity on the decolorization rate is more obvious, and such changes indicate that conductivity has a more significant effect on the decolorization rate of the original solution than pH, which is consistent with the analysis results in the table.
[0100] The present invention synthesizes Zn-doped Ni3S2 by a simple two-step hydrothermal method, and then modifies it by plasma to novel synthesize PA@Zn-Ni3S2 / NF, which can be used in energy and environment. Zinc is an effective promoter for regulating the OER performance of Ni3S2, and the Zn-doped Ni3S2 nanoarray only needs an overpotential of 192mV for oxygen evolution reaction after plasma modification, which is 35mV lower than that of Ni3S2 / NF nanoarray. Then, the plasma and the prepared catalytic agent are combined to degrade the dye by response surface method, and the initial solution concentration, voltage, pH and conductivity are selected as four factors affecting the degradation efficiency, among which the voltage has the most significant effect on the decolorization rate, and the pH has the least effect on the decolorization rate, and the degree of influence is arranged from large to small as voltage>initial concentration>conductivity>pH. Under the interaction of two factors, the joint effect of voltage and conductivity has the most significant effect on the degradation effect of the combined system, and the interaction of initial concentration and conductivity has the least effect on the decolorization of the dye solution. Comprehensively considered, the optimal degradation conditions are 94.91% when the initial concentration is 100 mg / L, pH is 7, voltage is 90 V, and conductivity is 1 mS / cm. The present invention provides an attractive low-cost catalytic degradation combined system and also opens up a new method for improving the activity of sulfide under the electrocatalytic action of zinc oxidation in water.
Claims
1. A method for preparing plasma-modified zinc-doped nickel sulfide for degrading acidic lake blue A wastewater, characterized in that: The following steps are involved: Step 1 Synthesis of nickel foam precursor: Dissolve Ni(CH3COO)2·4H2O, Zn(CH3COO)2·2H2O and urea in ultrapure water and stir to form a clear solution; Step 2: Transfer the above solution and the cleaned nickel foam into a stainless steel autoclave, and heat them at 110-130°C for 6-8 hours, and cool them naturally after the reaction is completed; Step 3: Take out the obtained NF, wash it with ultrapure water and ethanol three times, and dry it in a vacuum oven; Step 4: Immerse the nickel foam loaded with the precursor in a Na2S solution, and then place the reacted solution in a polytetrafluoroethylene In a lined stainless steel autoclave, react at 110-130°C for 3-5h, take out the nickel foam, wash and dry; Step 5: As a control, in step 1, Zn(CH3COO)2·2H2O was not added, and steps 1 to 4 were repeated to synthesize pure Ni3S2 / NF; Step 6: Cut off some of the synthesized zinc-doped nickel sulfide and transfer it to the center of the dielectric barrier discharge reactor. After pressing for 50-70s, PA@Zn-Ni3S2 / NF was obtained; In the step 1, Ni(CH3COO)2·4H2O is 1 mmol and has a mass of 0.249 g, Zn(CH3COO)2·2H2O is 0.1 mmol and has a mass of 0.0220 g, urea is 10 mmol and has a mass of 0.6 g, and ultrapure water is 40 mL; In the step 4, the concentration of the Na2S solution is 0.2 mol / L and the volume is 40 mL; In step six, the AC voltage is 70V.
2. The method for preparing plasma-modified zinc-doped nickel sulfide according to claim 1, characterized in that: In the step 2, the upper and lower bottom surfaces of the nickel foam are 3 cm×3 cm in size and 2 mm in thickness.
3. The method for preparing plasma-modified zinc-doped nickel sulfide according to claim 1, characterized in that: The stainless steel high-pressure reactor in step 2 is 50 mL.
4. The method for preparing plasma-modified zinc-doped nickel sulfide according to claim 1, characterized in that: In the step 3, the ethanol concentration is 95%; the drying temperature in the vacuum oven is 60° C. and the drying time is 2 h.
5. The method for preparing plasma-modified zinc-doped nickel sulfide according to claim 1, characterized in that: The stainless steel autoclave in step 4 is lined with polytetrafluoroethylene and has a volume of 50 mL.
6. The method for preparing plasma-modified zinc-doped nickel sulfide according to claim 1, characterized in that: The upper and lower bottom surfaces of the iron-doped nickel sulfide cut in step six are 1 cm×1 cm in size.
7. Use of plasma-modified zinc-doped nickel sulfide prepared according to the preparation method of claim 1 in degrading acidic lake blue A wastewater.